Teacher Deployment in Sierra Leone: Lessons learnt and going forward - Beoku-Betts, Iman (EdTech Hub, 2023)
This report provides an overview of the teacher deployment process in Sierra Leone prior to and including 2022. Through interviews with key stakeholders in the Ministry of Basic and Senior Secondary Education (MBSSE) and the Teaching Service Commission (TSC), we look at lessons learnt from the deployment process and next steps for how teacher deployment can be implemented. Although there are a number of volunteer teachers in Sierra Leone, the TSC are aiming to increase the number of qualified teachers on the government payroll as well as retaining teachers in rural areas. It was noted that teachers from rural areas being put on the government payroll and deployed to rural schools are better placed to teach in rural schools than teachers moving from urban to rural areas. Hpwever, it is still challenging to find qualified teachers in these rural areas. The TSC want to look at how they can target teachers to take up rural positions, either through distance learning to gain the right qualifications or working with teacher training institutions (TTIs) to prioritise schools in rural areas for placement. Overall, the TSC want to use data as the basis for decision-making on deploying teachers equitably. Keywords Teacher deployment; teacher training; unqualified teachers; volunteer teachers; rural schools; data for decision-making An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Low-Tech Devices and Connectivity for Learning in Lebanon - Chuang, Rachel; Khalayleh, Abdullah (EdTech Hub, 2021)
This document was produced in response to a request from the FCDO Lebanon team for guidance on leveraging low-tech devices and enabling connectivity to support learners in Lebanon, aligning with school reopenings. The document compiles effective initiatives across Lebanon and other countries.
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

EdTech Innovation for COVID-19: Insights from our global call for ideas - Plaut, Daniel; Carter, Alice; Dixon, Miranda; Salami, Taiye (EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _zenodo:submitted; _zenodoETH

Using EdTech in Settings of Fragility, Conflict and Violence: A Curated Resource List - Koomar, Saalim; Moss Coflan, Caitlin; Kaye, Tom (EdTech Hub, 2020)
This curated list of resources collates interventions that effectively deploy education technology in settings of fragility, conflict and violence (FCV). This list explores effective uses of EdTech in FCV settings, emphasising interventions and evidence relevant to the Yemeni context and distance learning during the Covid-19 crisis.
Keywords: C:Yemen; F: Helpdesk response; LP: English; W:Fragile and conflict affected contexts; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Investigating the Activity Levels of School Quality Assurance Officers in Sierra Leone - Beoku-Betts, Iman; Leh Wi Lan (EdTech Hub, 2023)
Since the launch of the Free Quality School Education (FQSE) Programme in 2018, the Sierra Leone Ministry of Basic and Senior Secondary Education (MBSSE) has prioritised the use of data for decision-making across several education reform programmes. Part of this vision has been to build systems to measure school quality through School Quality Assurance Officers (SQAOs) using data collection and feedback. This system includes using tools for teacher management, lesson observations, school improvement, and attendance monitoring. This report presents findings from qualitative research conducted in three districts in Sierra Leone. The aim is to provide the MBSSE and other partners with insights to understand the variation in and what is needed to maximise SQAO activity levels, increase principal engagement with digital tools, and support and promote quality visits to schools. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen